Optical edge effects create conjunctival indentation thickness artefacts. (9th February 2015) - Sorbara, Luigina; Simpson, Trefford L.; Maram, Jyotsna; Song, Eun Sun; Bizheva, Kostadinka; Hutchings, Natalie
Abstract: Purpose: Conjunctival compression observed in ultrahigh resolution optical coherence tomography (UHR‐OCT) images of contact lens edges could be actual tissue alteration, may be an optical artefact arising from the difference between the refractive indexes of the lens material and the conjunctival tissue, or could be a combination of the two. The purpose of this study is to image the artefact with contact lenses on a non‐biological (non‐indentable) medium and to determine the origins of the observed conjunctival compression. Methods: Two‐dimensional cross‐sectional images of the edges of a selection of marketed silicone hydrogel and hydrogel lenses (refractive index ranging from 1.40 to 1.43) were acquired with a research grade UHR‐OCT system. The lenses were placed on three continuous surfaces, a glass sphere (refractive index n = 1.52), a rigid contact lens ( n = 1.376) and the cornea of a healthy human subject (average n = 1.376). The displacement observed was analysed using ImageJ. Results: The observed optical displacement ranged between 5.39(0.06) μm with Acuvue Advance and 11.99(0.18) μm with Air Optix Night & Day when the lens was imaged on the glass reference sphere. Similarly, on a rigid contact lens displacement ranged between 5.51(0.03) and 9.72(0.12) μm. Displacement was also observed when the lenses were imaged on the human conjunctiva and ranged from 6.49(0.80) μm for the 1‐day Acuvue Moist to 17.4(0.22) μm for the Pure Vision contact lens. Conclusions: An optical displacement artefact was observed when imaging a contact lens on two rigid continuous surfaces with UHR‐OCT where compression or indentation of the surface could not have been a factor. Contact lenses imaged in situ also exhibited displacement at the intersection of the contact lens edge and the conjunctiva, likely a manifestation of both the artefact and compression of the conjunctiva.